The formation of abnormal ferrite in hypereutectoid steels revisited and its analogy to the formation of austenite and ferrite shells around graphite in cast irons - T. Chairuangsri (2018)
Abnormal ferrite, defined by large regions of ferrite covering coarse cementite, has been reported in hyper-eutectoid plain carbon, carburised and alloy steels. The early studies suggested that this abnormal ferrite might be a result of the coarsening of pearlite. A more radical view, expressed by Hillert in 1962, was that abnormal ferrite formed by nucleation and growth from cementite. In 2000, we reported further microstructural evidence for the occurrence of abnormal ferrite in hyper-eutectoid carbon steels and proposed an explanation based upon carbon redistribution accommodating concurrent growth of both cementite and abnormal ferrite. This explanation will be revisited and a comparison made with the formation of graphite and austenite in cast irons.